TINJAUAN PENGELOLAAN SENSUS HARIAN RAWAT INAP GUNA MENUNJANG SISTEM INFORMASI RUMAH SAKIT (RL1) DI RSAU Dr SALAMUN BANDUNG - Syaikhul Wahab (Jurnal Infokes, 2021)
This research was aimed to observe the management of daily inpatien census to suport the hospital information system (RL 1). The research method used was descriptive and qualitative method, while the data collection techniques used were by observation and literature study. The data management used manual collecting data. From the research it found that the procedure and the job desk was not made, daily inpatien census have not been accurate from collecting data, and late to collect the main data of inpatient census. The Suggestion that can be given by the writer that the hospital make job description and evaluate existing procedur, more carefull in filling data, and collect data quickly.